Propagation of Airy Gaussian vortex beams in uniaxial crystals - 余伟浩 赵瑞璜 邓富 黄加耀 陈迟到 杨湘波 赵燕平 邓冬梅 (Chinese physics B, 2016)
The propagation dynamics of the Airy Gaussian vortex beams in uniaxial crystals orthogonal to the optical axis has been investigated analytically and numerically. The propagation expression of the beams has been obtained. The propagation features of the Airy Gaussian vortex beams are shown with changes of the distribution factor and the ratio of the extraordinary refractive index to the ordinary refractive index. The correlations between the ratio and the maximum intensity value during the propagation, and its appearing distance have been investigated.